2009
DOI: 10.3415/vcot-08-06-0047
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intervertebral disk herniation associated with fused vertebrae treated by vertebral lateral corpectomy in a cat

Abstract: A 10-year-old Domestic Shorthair cat was admitted for chronic ambulatory paraparesis and a spinal malformation. The clinical examination revealed paraparesis accentuated on the left side. Thoracolumbar radiographs revealed a spinal malformation with a narrowed intervertebral space between L1 and L2, and a dorsal fusion at the level of L2-L3 with a common dorsal process. Magnetic resonance imaging (MRI) revealed an intervertebral disk herniation with a ventral compression of the spinal cord at the level of L1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…Logically a partial corpectomy would be more effective than a laminectomy to free the cord since the compression exerted by the thoracic hemivertebra is almost exclusively ventral. The other advantage of corpectomy over laminectomy is the lack of spinal cord manipulation and associated iatrogenic spinal cord trauma (9).…”
Section: Discussionmentioning
confidence: 99%
“…Logically a partial corpectomy would be more effective than a laminectomy to free the cord since the compression exerted by the thoracic hemivertebra is almost exclusively ventral. The other advantage of corpectomy over laminectomy is the lack of spinal cord manipulation and associated iatrogenic spinal cord trauma (9).…”
Section: Discussionmentioning
confidence: 99%
“…Although several reports describe the incidence, clinical presentation, imaging features, and clinical outcome of clinically significant feline IVDH, the evidence published on feline IVDH remains limited compared with that for dogs and man. Kathmann et al suggested a higher incidence of IVDH in purebred cats; British shorthairs and Persians were also overrepresented in a retrospective study of 31 cats with thoracolumbar (TL) IVDH .…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, IVDE (Hansen type I IVD disease) may be differentiated from IVDP (Hansen type II IVD disease) with 4 MRI variables; detection of a single IVDH and dispersion of the intervertebral disc (IVD) material beyond the IVD space are indicative of IVDE, whereas a midline IVDH and partial IVD degeneration are associated with the diagnosis of IVDP . Reports in the literature suggest that outcome for surgically treated feline IVDH is good, but no studies have focused specifically on feline IVDE.…”
Section: Introductionmentioning
confidence: 99%
“…Partial lateral corpectomy (PLC) may allow ventral decompression with minimal spinal cord manipulation . After technique introduction, subsequent descriptions of PLC were limited to research abstracts and 2 case reports in cats . More recently, slot morphometry and spinal cord decompression after PLC has been reported in 51 dogs and spinal stability after PLC was tested in vitro in 10 dogs …”
mentioning
confidence: 99%